2017
DOI: 10.1371/journal.pntd.0005223
|View full text |Cite|
|
Sign up to set email alerts
|

MLST-Based Population Genetic Analysis in a Global Context Reveals Clonality amongst Cryptococcus neoformans var. grubii VNI Isolates from HIV Patients in Southeastern Brazil

Abstract: Cryptococcosis is an important fungal infection in immunocompromised individuals, especially those infected with HIV. In Brazil, despite the free availability of antiretroviral therapy (ART) in the public health system, the mortality rate due to Cryptococcus neoformans meningitis is still high. To obtain a more detailed picture of the population genetic structure of this species in southeast Brazil, we studied 108 clinical isolates from 101 patients and 35 environmental isolates. Among the patients, 59% had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 95 publications
16
48
0
1
Order By: Relevance
“…As we have shown here and previously, the ST5 lineage is associated with apparently immunocompetent patients in Vietnam [25,53]. ST93 was the most prevalent sequence type in India, Indonesia, Uganda and Brazil (varying between 48% and 77%) [10,54,55], but accounted for less than 4% of isolates from Vietnam and Laos.…”
Section: Discussionsupporting
confidence: 67%
“…As we have shown here and previously, the ST5 lineage is associated with apparently immunocompetent patients in Vietnam [25,53]. ST93 was the most prevalent sequence type in India, Indonesia, Uganda and Brazil (varying between 48% and 77%) [10,54,55], but accounted for less than 4% of isolates from Vietnam and Laos.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, we observed differences in the disease progression/pathogenesis in mice infected with the three low virulence strains. One of the low virulence strains (UgCl223) had high terminal lung CFUs (1X 10 7 ) and very few CFUs in the spleen (10) and brain (10). Histologic examination of lung and brain from 2 additional animals revealed low numbers of cryptococci in the lung with moderate inflammation, and one mouse had small cryptococci infiltrating the meninges, scattered in small areas of necrosis within the neuropil.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that pathogen-specific characteristics, such as genotype or the degree of antigen shedding, influence immune responses to C. neoformans and the clinical outcome of infected patients (5, 79). Multi-locus sequence typing (MLST) of 7 genetic loci has been used previously to identify genetically similar strains (510). For example, studies of clinical isolates in both Uganda and Brazil showed higher patient mortality associated with sequence type 93 (ST93) strains (5, 10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain background can 96 significantly influence human disease, and there is tremendous disparity in strain frequency; 97 some strain groups are much more common than others. ST93 is common in Uganda, but is also 98 5 the most frequently isolated ST strain from HIV-infected patients in Brazil (85% [25,26]) and 99 India (71% [27,28]). Sequence type prevalence also has a clear geographic component as 100 different ST groups are dominant in other well-sampled countries (e.g., China, Thailand, 101 Vietnam, Indonesia, Botswana, France [27-29]).…”
mentioning
confidence: 99%